Eksperimentasi Model Pembelajaran Discovery Learning (DL) Dan Problem Based Learning (PBL) Berbasis Assessment For Learning (AFL) Terhadap Prestasi Belajar Matematika Ditinjau Dari Tingkat Motivasi Siswa - Fatimah, Siti, Dr. Sumardi, M.Si, M. Noor Kholid, S.Pd., M.Pd (2015)
The purpose of this study was to determine the effect of the difference-based learning model Discovery Learning Assessment for Learning and Problem Based Learning-based Assessment for Learning, motivation levels, as well as its interaction with mathematics achievement of students. This study was a quasiexperimental study with a 2 x 3 factorial design with the entire population of eighth grade students of SMP Muhammadiyah Surakarta 4 2014/2015 academic year. Sampling was done by cluster random sampling technique. The sample in this study amounted to 59 students. The research instrument is a test of learning and achievement motivation questionnaire. The test instrument achievement test and motivation questionnaire includes internal validation, external validation, and reliability. Test prerequisites include Lilliefors normality test method and test homogeneity of variance using Bartlett method. Balance test using the self-t. Test the hypothesis using two way analysis of variance with unequal cells. Based on hypothesis testing, research concluded that there are differences in the effects learning model Discovery Learning based Assessment for Learning and Problem Based Learning based Assessment for Learning on mathematics achievement, there are differences in the effect of the level of motivation on mathematics achievement, and there are no interaction Discovery Learning based Assessment for Learning and Problem Based Learning based Assessment for Learning and the level of motivation on mathematics achievement.